Radiation hardness study of positive LDO voltage regulators - Rybalka Sergey; Kulchenkov Evgeny; Demidov Andrey (EPJ Web of Conferences)
Two linear voltage regulators LS2-5V and LM2931 (output voltage of 5.0 V) were studied experimentally on their hardness to the radiation total ionizing dose (TID) effects. It was shown that output voltage changes lightly for LS2-5V at increasing of TID and not exceeds the operation mode limit (4.85 - 5.25 V). On the contrary, the output voltage value for LM2931 analogue exceeds operation mode limits at high TID that lead to its functional failure. It was found that both regulators functionate stably by consumption current parameter. Thus, LS2-5V demonstrates more stable functioning than LM2931 analogue. In addition, the SPICE macromodel for description of the radiation behavior by the output voltage parameter for LS2-5V was developed.